Classical Mechanics : A Textbook - Chandra, Suresh, 1938-, author 520527 (United Kingdom : Alpha Science, 2009)
Classical Mechanics: A Textbook begins with the elementary principles and introduces the generalised coordinates, Lagrangian formulation and Hamiltonian Formulation, as well as the Central Force used for derivation of Kepler's laws of planetary motion. The topic on Small Oscillations is introduced and applied for a number of systems and Rotational motion for a Rigid-body and High- speed motions are discussed under Special Relativity. The four vectors, four velocity, four momentum and so on, are also elucidated in a comprehensive manner.